Public food service communication field in the Chinese students’ linguistic consciousness: ethnocultural barriers and obstacles - Galina M. Vasilieva; Marina A. Chepinskaya; Jian Wang (Russian Language Studies, 2022)
The authors identify, classify and methodologically interpret communicative barriers and interferences arising for Chinese students in the sphere of catering, which is a fundamentally important culturally marked area of social and everyday communication. The relevance of this study is due to the significance and complexity of this social everyday sphere for the consciousness of foreign students, who face significant communicative barriers and obstacles that require methodological interpretation and consideration in the content of teaching Russian as a foreign language. The aims of this work are to identify and methodo- logically interpret communicative barriers of Chinese students in everyday communication (on the material of catering sphere), and to establish their correlations with the phenomena of lexical asymmetry. The main methods used in the research: mathematical processing of the obtained data, questionnaires, component analysis of vocabulary and comparison. The research material includes the results of the questionnaire aimed at identifying the barriers and obstacles encountered by Chinese students in the field of catering. It was determined that barriers and interference related to catering communication occurred for more than 75% of the students. Quantitative and meaningful processing of the questionnaire materials demonstrated that barriers and interference appeared in three main aspects: ethnographic, ethno- psychological, and ethnolinguistic. Methodologically oriented interpretation of communicative barriers is based on their correlation with the facts of the language. The integrative approach to the word taking into account its linguistic and extra-linguistic content determined which components of its structure translate ethnographic, ethnopsychological and ethnolinguistic differences of Russian and Chinese linguistic cultures that create communicative barriers. That is why the process of Russian language teaching considers conceptual, proper-lexical, semantic, connotative, background and contextual lacunas. Considering asymmetrical phenomena in the content of vocabulary teaching allows reducing the level of ethnographic, ethnopsychological and ethnolinguistic barriers and hindrances that arise for Chinese students in the sphere of catering. The prospects of the research include creation of the training dictionary “Gastronomic Culture Code in Language Vocabulary,” aimed at the Chinese students studying Russian.